Cultivation of pineapple as a function of the splitting of top-dressing potassium fertilization (Research, Society and Development, 2021)
In agriculture, horticulture constitutes a field of great importance. The pineapple is among the tropical fruit species in economic and social importance in most developed countries of tropical and subtropical climate. Brazil is one of the largest producers of pineapple. So is need for more research on this fruit, to choose the best dose of potassium coverage and floral induction, and therefore maximize production, giving the possibility of spreading the harvest. The objective of this study was to investigate the development of Perola pineapple at different doses of potassium fertilizers in coverage, and evaluating their effects on fruit yield in dryland farming in the municipality of Alta Floresta, MT. The experimental design was a randomized block design in 3 x 2 factorial design, with 24 treatments, consisting of 3 doses of potassium (0, 10 and 20 g plant-1), 2 fertilization intervals (30 and 60). Under the conditions of this study, it was concluded that the best dose of potassium chloride in coverage for Perola pineapple, fruit color variables, average fruit diameter and average fruit weight is 120 g per plant. The range more suitable for the application of K was 60 days.